Virtual Reality-Based Attention Bias Modification Training for Social Anxiety: A Feasibility and Proof of Concept Study - Urech, Antoine; Krieger, Tobias; Chesham, Alvin; Mast, Fred W.; Berger, Thomas (Frontiers in Psychiatry, 2015)
Attention bias modification (ABM) programs have been considered as a promising new approach for the treatment of various disorders, including social anxiety disorder (SAD). However, previous studies yielded ambiguous results regarding the efficacy of ABM in SAD. The present proof-of-concept study investigates the feasibility of a newly developed virtual reality (VR)-based dot-probe training paradigm. It was designed to facilitate attentional disengagement from threatening stimuli in socially anxious individuals (N=15). The following outcomes were examined: (a) self-reports of enjoyment, motivation, flow and presence, (b) attentional bias for social stimuli, and (c) social anxiety symptoms. Results showed that ABM training is associated with high scores in enjoyment, motivation, flow and presence. Furthermore, significant improvements in terms of attention bias and social anxiety symptoms were observed from pre- to follow-up assessment. The study suggests that VR is a feasible and presumably a promising new medium for ABM trainings. Controlled studies will need to be carried out.